1998
DOI: 10.1002/hep.510270311
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell depletion partially prevents hepatic heme oxygenase 1 messenger RNA accumulation in systemic inflammation in mice: Role of interleukin 1β

Abstract: The heme oxygenase 1 (HO-1) gene is rapidly activated in the liver after lipopolysaccharide (LPS) treatment. Ninety minutes after LPS treatment (0.1 mg/kg, intraperitoneally) hepatic HO-1 messenger RNA (mRNA) of mice was 40 times the control value. To investigate the hepatic cellular source of the increased HO-1 transcript, we treated mice with LPS and galactosamine (700 mg/kg, intraperitoneally), a selective transcriptional inhibitor of hepatocytes. Galactosamine prevented the LPS-mediated increase of HO-1 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 50 publications
(52 reference statements)
3
39
0
2
Order By: Relevance
“…In our study, gadolinium administration does not seem to affect cytokine release in tissues outside the liver, since it did not modify serum concentrations of TNF-after LPS injection. Similar results have previously been observed by other authors (Kohno et al 1997, Rizzardini et al 1998, Kono et al 2001. Furthermore, Kono et al (2002) have reported that although gadolinium administration prevented LPS-induced increase in TNF-gene expression in the liver, it did not modify the serum concentrations of TNF-.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, gadolinium administration does not seem to affect cytokine release in tissues outside the liver, since it did not modify serum concentrations of TNF-after LPS injection. Similar results have previously been observed by other authors (Kohno et al 1997, Rizzardini et al 1998, Kono et al 2001. Furthermore, Kono et al (2002) have reported that although gadolinium administration prevented LPS-induced increase in TNF-gene expression in the liver, it did not modify the serum concentrations of TNF-.…”
Section: Discussionsupporting
confidence: 89%
“…Methyl palmitate (2 g/kg, i.v) was applied as an effective kupffer cells inhibitor and administered 44 hours before LPS. 30 Liver injury biomarkers were assessed 24 hours after antimalarial drugs administration in all experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…4 HO-1 expression is induced not only in response to its substrate heme, 8 but also by various stress stimuli such as hydrogen peroxide, xenobiotics, nitric oxide, ultraviolet-A radiation, heavy metals, hypoxia, hyperoxia, heat shock, 9,10 endotoxin 11,12 and proinflammatory cytokines. [13][14][15][16] Accumulating evidence reveals the protective role of HO-1 by virtue of the antiinflammatory, antiapoptotic and antiproliferative activities of the products released by the heme breakdown reaction. [17][18][19] The acute phase response (APR) is a defense reaction of the organism directed to restrict the area of damage and to eliminate, or at least isolate, the damaging agent.…”
mentioning
confidence: 99%
“…Although it has been shown that HO-1 could be upregulated under inflammatory conditions in the liver 15,16,22 and in hepatoma cell lines, 14 it remains unclear whether induction of HO-1 in vivo occurs as a response to cytokines released locally at the site of inflammation. To test this hypothesis, we analyzed HO-1 expression in the liver and extrahepatic tissues of rats after induction of sterile muscle abscess by injection of turpentine oil (TO), which subsequently leads to a local inflammation followed by systemic APR.…”
mentioning
confidence: 99%